Competitive strategy of halal tourism in Riau: opportunities and challenges - Mardatillah, Annisa (Jurnal Pariwisata Pesona, 2023)
The halal tourism sector is currently a hot issue that is still being studied from various scientific approaches. Therefore, this study aims to systematically analyze the SWOT analysis of the results of identifying various internal and external factors of halal tourism in Riau Province. Then it is used in formulating a marketing strategy for halal tourism in Riau Province to achieve sustainable competitive advantage. The respondents of this study consisted of six people selected by the purposive sampling technique. The potential for unique values and originality from the historical background of Islam and Islamic Malay culture in Riau Province becomes a strong potential in responding to competition challenges in the halal tourism business sector. Observations, interviews, and documentation are used in collecting research data. The results of this study contribute to the determination of strategies for the growth and development of halal tourism in Riau Province to be increasingly competitive. Availability of Halal Certified and Availability of Islamic History and Cultural Attractions Based on Local Wisdom as an internal strengths can grow and develop as opportunity. Transportation connectivity is not optimal as a weakness need to develop in internal factor. Communication network need to grow and develop for gaining the threat.